Consider All Stakeholders in Quality Assurance of Preprofessional Education. (December 2017) - Gambescia, Stephen F.; Early, Jody O.
This commentary explains (via a schematic and some detail) that quality assurance in the teaching and learning process is not a hierarchical relationship among stakeholders but rather an ongoing review, discussion, and set of quality improvement and capacity building actions among stakeholders. These stakeholders include employers, professional membership associations, accrediting bodies, the public, individual certifying entities, and providers of higher education. Each group has its value-added contribution and sphere of influence in the education quality assurance process, especially during times of change. Each group has its understandable needs, capacity for contributions, and limitations when changes are being made. The nature and extent of the influence of each group will change, but the key is to consider all stakeholders and their interests to improve the practice of the individual health professional.